2022
DOI: 10.3389/fvets.2022.902001
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome-Metabolome Responses in Ruminal Content and Feces of Lactating Dairy Cows With N-Carbamylglutamate Supplementation Under Heat Stress

Abstract: The objective of the present study was to investigate the effects of N-carbamylglutamate (NCG) supplementation on metabolic profile and microbiota in ruminal content and feces of lactating dairy cows under heat stress (HS). Forty-eight lactating Holstein cows (154 ± 13.6 days in milk) were assigned randomly to four treatments (n = 12), to receive 0, 15, 20, or 25 g/day of commercial NCG (proportion: 97.7%) for the period of 60 days. The recorded ambient temperature–humidity index (THI) suggested that the cows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Observations by Zhang et al ( 16 ) demonstrated that dietary NCG supplementation ameliorated the diminished abundance of Clostridium , Lactobacillus , and Streptococcus within the colonic mucosa of lambs beset by intrauterine growth restriction. Likewise, Li et al ( 17 ) noted that NCG supplementation invoked an elevation in unidentified_Prevotellaceae coupled with a decrease in Acetitomaculum , Marvinbryantia , and unidentified_Christensenellaceae within the fecal microbiome of heat-stressed lactating dairy cows. In line with this, our investigation revealed a consistent pattern of effects following NCG supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Observations by Zhang et al ( 16 ) demonstrated that dietary NCG supplementation ameliorated the diminished abundance of Clostridium , Lactobacillus , and Streptococcus within the colonic mucosa of lambs beset by intrauterine growth restriction. Likewise, Li et al ( 17 ) noted that NCG supplementation invoked an elevation in unidentified_Prevotellaceae coupled with a decrease in Acetitomaculum , Marvinbryantia , and unidentified_Christensenellaceae within the fecal microbiome of heat-stressed lactating dairy cows. In line with this, our investigation revealed a consistent pattern of effects following NCG supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the abundance of Blautia was lower in heifers fed a high forage diet for breeding than in those fed the late fattening diet including high concentrate. Marvinbryantia , which is present in the human gut and has the ability to degrade cellulose [ 40 ], was also found in the feces of cattle [ 41 ]. Since Marvinbryantia is more abundant in early fattening heifers than in early fattening steers, this genus may be affected by gender.…”
Section: Discussionmentioning
confidence: 99%